Explosion systems with inert high-modulus components : increasing the efficiency of blast technologies and their applications - Balagansky, I. A. 1952-; Bataev, A. A.; Bataev, I. A. (Wiley, 2019)
Describes in one volume the data received during experiments on detonation in high explosive charges This book brings together, in one volume, information normally covered in a series of journal articles on high explosive detonation tests, so that developers can create new explosive technologies. It focuses on the charges that contain inert elements made of materials in which a sound velocity is significantly higher than a detonation velocity. It also summarizes the results of experimental, numerical, and theoretical investigations of explosion systems, which contain high modulus ceramic components. The phenomena occurring in such systems are described in detail: desensitization of high explosives, nonstationary detonation processes, energy focusing, and Mach stems formation. Formation of hypersonic flows of ceramic particles arising due to explosive collapse of ceramic tubes is another example of the issues discussed. Explosion Systems with Inert High Modulus Components: Increasing the Efficiency of Blast Technologies and Their Applications also looks at the design of explosion protective structures based on high modulus ceramic materials. The structural transformations, caused in metallic materials by the energy focusing, or by the impact of hypersonic ceramic jets are also discussed. These transformations include, but not limited to adiabatic shear banding, phase transformations, mechanical twinning, melting, boiling, and even evaporation of the impacted substrates.-Specifically discusses in one volume the explosions involved with inert high modules components normally scattered over numerous journal articles -Covers methods to increase energy output of a weak explosive by encasing it in a higher explosive -Discusses the specifics of explosive systems containing high modulus inert elements -Details the process of detonation and related phenomena, as well as the design of novel highly performant explosive systems -Describes the transformation in materials impacted due to explosion in such systems Explosion Systems with Inert High Modulus Components will be of great interest to specialists working in fields of energy of the explosion and explosion safety as well as university staff, students, and postgraduate students studying explosion phenomena, explosive technologies, explosion safety, and materials science.
Keywords: Detonation waves.; Explosions.; Blast effect.; Fracture mechanics.; Shaped charges.; elektronické knihy; electronic books